The mediating effect of traditional Chinese medicine (TCM) health literacy between TCM culture promotion and residents' health status - Zhang, Xiaofan; Hong, Xiang; Zhang, Zongming (Frontiers in Public Health, 2024)
Background: Traditional Chinese medicine (TCM) is a medical system with a long history and unique theories and techniques, playing a crucial role in maintaining and promoting human health. Disseminating TCM cultural knowledge is essential for enhancing the TCM health literacy and health status of people. This study aimed to investigate how TCM health literacy mediated the relationship between the TCM cultural ambiance and people’s health status. Methods: A multi-stage random sampling method was employed to select 22,125 permanent residents in Jiangsu Province for a survey aimed at examining the popularization of TCM culture. The survey categorized the intensity of TCM cultural ambiance into four grades (0–3) based on the promotion activities in various settings, including street/community, medical service institutions, and educational/work institutions. Furthermore, the survey evaluated TCM health literacy, overall health status, and prevalence of chronic diseases using the 2017 Chinese Citizens TCM Health Literacy Survey Questionnaire. Results: A positive correlation was observed between cultural promotion ambiance and TCM health literacy. The impact of the cultural promotion ambiance on health literacy also increased with the increase in promotion grade (P < 0.001). The correlation analysis showed no statistically significant correlation of promotion grade 1 [β = 0.21, 95% confidence interval (CI): -0.26 to 0.67] with the health status of residents, whereas promotion grades 2 (β = 1.47, 95% CI: 1.12–1.83) and 3 (β = 4.61, 95% CI: 4.19–5.04) were positively correlated with self-health evaluation. TCM health literacy was positively correlated with self-health evaluation (β = 2.10, 95% CI: 1.72–2.48) and negatively correlated with the risk of chronic diseases (odds ratio = 0.53, 95% CI: 0.48–0.58). The analysis of the mediating effect revealed that the TCM cultural ambiance directly impacted self-health evaluation and the prevalence of chronic diseases, with coefficients of 1.131 and –0.027 (P < 0.001), respectively. Conclusions: TCM health literacy served as a mediating factor in the positive relationship between the TCM cultural ambiance and health status. Theoretically, it can improve the overall health of residents by intensifying the dissemination of TCM culture and enhancing their health literacy.